Slapping automatism in epileptic seizures: a case series - Shenglin Hao; Ziyi Feng; Haifeng Zhao; Wei Liu; Shikun Zhan; Bomin Sun; Qiang Zhou; Chunyan Cao (Frontiers in Human Neuroscience)
BackgroundSlapping automatism is a type of automatism observed during epileptic seizures, but its underlying electrophysiological mechanisms remain poorly understood. Stereo-electroencephalography (SEEG) provides a unique opportunity to investigate the associated cortical areas with epileptiform discharges during the slapping automatism.Case reportWe report five cases of drug-resistant epilepsy in which SEEG recordings captured slapping automatism. In four patients, slapping movements coincided with ictal electrical evolution in the prefrontal lobe, specifically involving the orbitofrontal cortex (OFC), lateral prefrontal cortex (PFC), and anterior cingulate (ACC). Among them, two cases were temporal lobe epilepsy (TLE), while the other two were frontal lobe epilepsy (FLE). Additionally, we describe one patient with TLE and obsessive-compulsive disorder (OCD), whose SEEG recordings revealed frequent interictal epileptiform discharges in both the medial temporal and prefrontal regions. The seizures originated in the temporal lobe and rapidly evolved into generalized seizures. Although slapping automatism was not observed during seizures, the patient exhibited repetitive patting on the bed during the interictal period. Based on SEEG-defined epileptic networks, all patients underwent surgical interventions, including lesion resection and/or disconnection procedures. At follow-up, all three patients achieved Engel class I outcomes and two patients Engel class II.ConclusionSEEG recordings in this study confirm a strong association between orbitofrontal lobe epileptic activity and slapping automatism. Notably, we report a case of TLE with comorbid OCD, characterized by frequent epileptiform discharges in the orbitofrontal lobe, providing direct electrophysiological evidence of prefrontal abnormalities in OCD. Together, these findings highlight a shared pathological network of orbitofrontal-striatal-pallidal-thalamic between frontal and temporal epilepsy with slapping automatism and OCD.